(untitled) (Research Announcements "Heritage BG", 2023)
The article does not take a position against the care for monuments that are being ignored and are suffering neglect and decay in the past decades, but instead is exploring what is the narrative that is pushed to the surface in the absence ofstate care. Research on the built environment and the monumental landscape in Southern and Southwestern Bulgaria is significant for the general social, internal and external political spheres due to its border positionality1 and historically loaded past. While we were evaluating the general condition of the immovable cultural properties of local importance (ICPLI) in the Municipality and the state of its management, I was enticed to search for the political agents that ‘claim’ authority over it (instead of the state) and to evaluate whose story do the local people ‘see and hear’ on an everyday basis. The article does not take a position against the care for monuments that are being ignored and are suffering neglect and decay in the past decades, but instead is exploring what is the narrative that is pushed to the surface in the absence of state care. References: Gruev, M. (2011). Насилие и политика: Пиринска Македония в етнонационалните политики на комунистическия режим в България. В: Насилие, политика и памет. Комунистическият режим в Пиринска Македония – рефлексии на съвременника и изследователя. (съст. Михаил Груев, Веселин Тепавичаров, Петя Василева-Груева, Виолета Коцева – Попова, Мария Костадинова). София. News.bg (08.03.2023). ВМРО искат Комплекс на основателите да замести МОЧА. Available at: https://news.bg/regions/vmro-iskat-kompleks-na-osnovatelite-da-zamesti-mocha.html (accessed 01.06.2023). Pzdnes.com (18.03.2019). Македонски туристи трият „българска Македония“ на гроба на Яне Сандански. Available at: https://shorturl.at/ltJZ6 (accessed 01.06.2023). Standart (31.05.2022). ВМРО акция за героите. Цветя на всеки паметник. Available at: https://www.standartnews.com/balgariya-politika/vmro-s-aktsiya-za-geroite-tsvetya-na-vseki-pametnik-494202.html (accessed 01.06.2023). Struma.com (02.11.2010). ВМРО реставрира паметника на Стою Хаджиев и каменния мост в центъра на Голешово. Available at: https://www.struma.com/obshtestvo/7-gardove-s-nagradi-za-otlichna-rabota_12935/ (accessed 01.06.2023). VMRO (02.11.2010). Мост и паметник в Голешово откри ВМРО. Available at: https://vmro.bg/most-i-pametnik-v-goleshovo-otkri-vmro (accessed 01.06.2023). Bellentani, F., & Panico, M. (2016). The Meanings of Monuments and Memorials: Toward a Semiotic Approach. – Punctum, 2(1): 28-46. Billig, M. (1995). Banal Nationalism. London/Thousand Oaks/New Delhi: Sage Publications. Giddens, A. (1979). Central Problems in Social Theory: Action, structure and contradiction in social analysis: Action, Structure and Contradictions in Social Analysis. London: Palgrave Macmillan. Giddens, A. (1984). The Constitution of Society. Outline of the Structuration theory. Berkeley/Los Angeles: University of California Press. Interim report (2022). Interim Report (documentary analysis) Analytical Study on the Project ‘Policies for the Conservation and Promotion of Immovable Cultural Property of Local Importance in Bulgaria. Ethnological Analysis on the Examples of the Municipalities of Balchik, Kavarna, Garmen and Sandanski’. Draft. Jones, P. (2011). The Sociology of Architecture: Constructing Identities. Liverpool: Liverpool University Press. Lefebvre, H. (2003). The Urban Revolution. USA: The University of Minnesota. Renan, E. (1992). What is a Nation? Paris, Presses-Pocket, 1992 (translated by Ethan Rundell). Retrieved from: http://ucparis.fr/files/9313/6549/9943/What_is_a_Nation.pdf (accessed 01.06.2023). Todorova, M. (1997). Ethnicity, Nationalism, and the Communist Legacy in Eastern Europe. – East European Politics and Societies, Vol 7, No 1. Verdery, K. (1999). The Political Lives of Dead bodies. USA: Columbia University Press. Vitale, F. (2012). The Ethics of Space: Jaques Derrida and the architecture to come. International Society for the Philosophy of Architecture. Available at: http://isparchitecture.com/the-ethics-of-space-jaques-derrida-and-the-architecture-to-come-by-francesco-vitale/ (accessed 11.09.2016).